Eksplorasi Ketangguhan Mental dan Kecemasan Kompetitif pada Atlet Arung Jeram di Jakarta - Nurcahyadi, Muhammad Fixi; Trihandayani, Dewi (Fakultas Psikologi Universitas YARSI, 2024)
In every sports competition, psychological aspects such as mental toughness and competitive anxiety play a crucial role in determining an athlete's success. Research related to mental toughness associated with competitive anxiety among rafting athletes is still limited. This study aims to examine the relationship between mental toughness and competitive anxiety in rafting athletes who are members of the Indonesian Rafting Federation (FAJI) in Jakarta. The study involved 35 rafting athletes, consisting of 13 males and 22 females, aged between 18 and 25 years. The instruments used to measure the variables in this study were the Mental Toughness Scale and the Competitive Anxiety Scale. The data collected were analyzed using Pearson's product-moment correlation in SPSS 26.0. The results of the analysis showed a significant negative relationship between mental toughness and competitive anxiety (r = -0.48, p < .003). These findings indicate that an increase in mental toughness is associated with a decrease in the level of competitive anxiety in Jakarta rafting athletes. The implications of these results highlight the importance of developing mental toughness as a strategy to reduce anxiety and enhance performance in competitive contexts.